MANAJEMEN PERBATASAN FOKUS INOVASI PENDIDIKAN DI PERBATASAN KALIMANTAN UTARA (BORDER MANAGEMENT FOCUS INNOVATION EDUCATION IN NORTH KALIMANTAN BORDER) - Lia Rosliana, Fani Heru W, Wildan Lutfie , Kemal Hidayah dan Tri Noor Aziza (Puslatbang KDOD Lembaga Administrasi Negara, 2015)
The aims in this study was to analyze the optimization of acceleration of the settlement of issues of border management education innovation in North Borneo, and education model that can be applied at the borders between countries. Type of research is descriptive qualitative, data collection by in-depth interview, observation and documentary research. Data mining done purposively through the mechanism of indepth interviews with snowball sampling. The conclusion from this study is that there are three innovations in northern borneo border, namely : sekolah tapal batas, The Filial Svhool and undergraduate teaching. Rekomendations innovation model that can be applied at the border include the scope of innovation of teaghers, students and civil society, innovation scope of the facilities, and the scope curriculum innovation.Keywords : Border Management, Innovation Education, Innovation ModelTujuan dalam kajian ini adalah menganalisis optimalisasi percepatan penyelesaian isu-isu pengelolaan perbatasan inovasi pendidikan yang ada di Kalimantan Utara serta model inovasi pendidikan yang dapat diterapkan di perbatasan antar negara. Jenis penelitian yang dilakukan yaitu kualitatif-deskriptif. Pengumpulan data dengan cara in-depth interview, observation dan documentary research. Penggalian data dilakukan secara purposive melalui mekanisme in-depth interview dengan snowball sampling. Kesimpulan dari Kajian ini adalah terdapat tiga buah inovasi yang ada di perbatasan kalimantan utara yaitu: sekolah tapal batas, sekolah filial serta sarjana mengajar. Rekomendasi model inovasi yang dapat diterapkan diperbatasan meliputi inovasi lingkup guru, siswa dan sosial masyarakat, inovasi lingkup fasilitas, dan inovasi lingkup kurikulum. Kata Kunci: Manajemen Perbatasan, Inovasi Pendidikan, Model Inovasi